MYTHS IN EDGAR ALLAN POEâ€™S â€œTHE RAVENâ€ - Harits, Imron Wakhid; Sari, Ulfah Rizkyanita (Universitas Negeri Semarang, 2016)
This study is aimed to describe myths which appear in Edgar Allan Poe‘s ―The Raven‖ and to figure out the way that is used by Edgar Allan Poe to show the myths in the poem and convey the meaning of the poem itself. Archetype theory from Canadian critic Northrop Frye is used in this study in order to analyze the myths in ―The Raven‖ poem. Furthermore, to clarify the myths in the poem itself, this study uses a qualitative research as a method to collect, select, code, and analyze the data. In the research finding ―The Raven‖ poem by Edgar Allan Poe contains three types of archetype imagery, they are apocalyptic, demonic, and analogical imagery (analogy of innocence and analogy of experience). This poem also contains the four types of cyclical symbolism of archetype, they are divine world, human world, animal world, and mineral world. It is also found that this poem has a structure of sparagmos due to the dark myth and the confusion world that cover the theme of poem. Finally, this poem is divided into six phases of winter which is related to the literary genre of irony and satire that explain more about the sorrowfulness of the author, Edgar Allan Poe because his lover, Lenore leaves him.